Does College Guarantee Economic Mobility? : Incorporating Lost In-kind Benefits into the Calculation (Higher Education Politics and Economics, 2025)
Average salaries of college graduates are higher than salaries of those without degrees. However, the experience of graduating and out-earning the income requirements for in-kind or entitlement benefits like Medicaid, public assistance, Supplemental Nutritional Assistance Plan, and/or Section 8 housing vouchers are not taken into consideration in any mobility calculation nor are students prepared to lose their benefits. Teaching at an urban commuter school in a financially disadvantage borough, I have identified a gap in the research literature and supportive services for these low-income students. This opinion piece further describes the problem and highlights areas for future action and research.